SKILL MISMATCH DAN UPAYA MENGATASINYA (Studi pada 3 hotel di Semarang) - Christantius Dwiatmadja; Yustina Erti Pravitasmara Dewi (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2018)
This study aims to explain how to overcome the employee skill mismatch that works with the company. The research was conducted at the hotel because of the high of its business competition and the gap between the number of hospitality education institutions and the number of hotels in operation that had consequences for the occurrence of skill mismatch. The findings of a previous study of skill mismatch concluded that there was a disruption in competitiveness and productivity in companies using employees with skills and education gaps. Using a multi-case study technique, data collection was carried out in five-star hotels, three-star hotels and one-month period June-August 2018 in Semarang. The results of the study show that the effort to overcome the mismatch skill in the company is to conduct employee learning. There are differences in the learning process of employees in overcoming skill mismatch, where the higher the star classification in the hotel business the higher the involvement of the company. In other words, the smaller the classification of hotel stars, the individual efforts of employees to learn to overcome the mismatch skill is also greater. Based on these findings, this study uses the learning organization theory as a frame of mind and analysis.